Bunt w Sucro 206 r. p.n.e. - czyli społeczne koszty budowy imperium - Maciejowski, Maciej (Studia Europaea Gnesnensia, 2010)
The article addresses the issue of relations between Rome and its provinces on the example of the community of legionnaires serving on the Iberian Peninsula. The legion service was not limited to the military aspect, which is manifested in the numerous mutinies of the soldiers. By juxtaposing the account of chroniclers of the period with the findings of contemporary historians concerning the causes of mutinies the author presents the material and social dimension of Roman expansion.